The Impact of Integrating Quizizz Lesson Mode and Paper Mode on EFL Students’ Reading Comprehension of Procedure Texts - Ricky Jonathan; Novitri Novitri; Maria Safriyanti (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Reading comprehension plays a crucial role in learning English as a Foreign Language (EFL), particularly when students engage with procedure texts. Although interactive and student-centered approaches are strongly advocated, traditional teaching methods still dominate classroom practice, often positioning students as passive learners and resulting in low engagement and limited comprehension. Grounded in gamification theory and constructivist principles, this study investigates the integration of Quizizz Lesson Mode as instructional scaffolding and Quizizz Paper Mode as formative assessment to enhance students’ reading comprehension. Employing a pre-experimental one-group pretest–posttest design, the study involved 38 students from class X.7. The findings revealed a statistically significant improvement in students’ reading comprehension, with a large effect size (Cohen’s d = −1.005), indicating substantial learning gains. Classroom observations further demonstrated that the combined use of Lesson and Paper Modes increased student engagement, minimized performance gaps, and provided immediate feedback, thereby transforming assessment into an integral and less stressful component of the learning process. These results contribute to gamification research by illustrating how digital platforms can seamlessly integrate instruction and assessment within a continuous learning cycle. Practically, the study recommends that teachers incorporate Quizizz into core instructional activities and adapt the Lesson–Paper Mode strategy for other text genres. Future research should adopt controlled experimental designs to examine long-term effects and broader pedagogical applications.